2014
DOI: 10.1016/j.resuscitation.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular blockade during therapeutic hypothermia after cardiac arrest: Observational study of neurological and infectious outcomes

Abstract: Continuous intravenous NMB during TH after cardiac arrest has potential owns effects on ICU survival with a trend increase in the frequency of early-onset pneumonia. Randomised controlled trials are needed to define the role for NMB among treatments for TH-induced shivering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 40 publications
1
41
1
1
Order By: Relevance
“…NMB administration in TH not only decreases refractory shivering but also facilitates both the rapid achievement and maintenance of the target temperature. A recent report suggests that continuous intravenous NMB therapy has a beneficial effect on the survival of patients undergoing post-cardiac arrest TH [ 30 ]. However, the same study also reported that NMB therapy is associated with a non-significant increase in the frequency of early-onset pneumonia [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…NMB administration in TH not only decreases refractory shivering but also facilitates both the rapid achievement and maintenance of the target temperature. A recent report suggests that continuous intravenous NMB therapy has a beneficial effect on the survival of patients undergoing post-cardiac arrest TH [ 30 ]. However, the same study also reported that NMB therapy is associated with a non-significant increase in the frequency of early-onset pneumonia [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Persistent shivering is treated according to a previously published three-step protocol [ 53 ] that has been adapted since the publication of the Bedside Shivering Assessment Score (BSAS) [ 54 , 55 ]. The goal is to obtain a BSAS ≤1.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…27 Likewise, in patients with cardiac arrest, continuous infusion of neuromuscular blocking drugs during therapeutic hypothermia was associated with more frequent early-onset pneumonia. 28 A recent trial of neuromuscular blockade for ARDS did not report increased risk of ventilator-associated pneumonia with the use of cisatracurium. 8 In theory, corticosteroids may favor the recruitment of T helper (Th) type 2 cells rather than Th1 cells.…”
Section: Secondary Infectionsmentioning
confidence: 99%